2020
DOI: 10.3389/fped.2020.00566
|View full text |Cite
|
Sign up to set email alerts
|

Association of Antibiotics Administration Timing With Mortality in Children With Sepsis in a Tertiary Care Hospital of a Developing Country

Abstract: Objective: To investigate the association between antibiotics administration timing with morbidity and mortality in children with severe sepsis and septic shock, presenting to a tertiary care center in a developing country. Methods: This is a retrospective study of children aged 14 years or younger diagnosed with severe sepsis or septic shock at a free-standing tertiary children's hospital in Saudi Arabia between April 2015 and February 2018. We investigated the association between antibiotic administration ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…A study conducted by Hassan et al to assess the feasibility and efficacy of sepsis management guidelines in the PICU revealed a mortality rate of 47.8 and 26.2%, before and after implementing the guidelines, respectively [ 8 ]. Another study conducted in a tertiary PICU in Riyadh reported an overall mortality rate of 17.9% for severe sepsis and septic shock [ 6 ]. Moreover, in Egypt, the mortality rate of sepsis has been reported as 28.1 and 8.8% by Bekhit et al and El-Mashad et al, respectively [ 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted by Hassan et al to assess the feasibility and efficacy of sepsis management guidelines in the PICU revealed a mortality rate of 47.8 and 26.2%, before and after implementing the guidelines, respectively [ 8 ]. Another study conducted in a tertiary PICU in Riyadh reported an overall mortality rate of 17.9% for severe sepsis and septic shock [ 6 ]. Moreover, in Egypt, the mortality rate of sepsis has been reported as 28.1 and 8.8% by Bekhit et al and El-Mashad et al, respectively [ 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in mortality rate between patients with early versus delayed antibiotic administration, which could be attributed to the small number of enrolled patients and the underpowered design of the study. However, a study conducted by Alsadoon et al in Riyadh, Saudi Arabia reported delayed antibiotic administration was not significantly associated with higher PICU mortality in children diagnosed with severe sepsis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies support the recommendation of antibiotic prescription within the first hour of sepsis identification ( 4 , 12 ). Most patients in both studies had severe disease, with 69% ( 4 ) and 79% ( 12 ) with septic shock, respectively.…”
Section: Antibiotics: Step By Stepmentioning
confidence: 94%
“…Timely prescription of antimicrobials is one of the main goals to prevent mortality ( 11 ). Especially for patients with shock and end-organ disfunction, the ideal moment for receiving antibiotics is within the first hour of health assistance ( 4 , 5 , 12 , 13 ). However, the indiscriminate use of antibiotics can lead to increased resistance, risk of Clostridioides difficile infection, as well as drug related toxicity (acute kidney injury, diarrhea, cytopenia, skin rash and anaphylaxis) ( 7 , 9 ).…”
Section: Antibiotics: Step By Stepmentioning
confidence: 99%